The Effect of Leadership Style, Motivation and Job Satisfaction on Management Performance in Employee Cooperatives in South Tangerang - Yusup Agung Wirastomo; Fadhilah Izhari; Cecep Yoto Haryoto (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
Performance is the achievement of work results in quality and quantity. There are many factors or variables that affect performance. The independent variables in this study include leadership style, motivation and job satisfaction. This study aims to determine the effect of leadership style, motivation, and job satisfaction on the performance of management in employee cooperatives in South Tangerang. In this research, the type of research used is associative research. The results of this study, first, leadership style has a positive and significant effect on the performance of the board. Second, motivation has a positive and significant effect on management performance. Third, job satisfaction has a positive and significant effect on management performance. Fourth, leadership style, motivation, and job satisfaction jointly affect the performance of management in employee cooperatives in South Tangerang.